230k views
3 votes
Enter the values for the highlighted variables to complete the steps to the sum (3x)/(2x - 6) + 9/(6 - 2x) = (3x)/(2x - 6) + 9/(a(2x - 6)) = 3x 2x-6 + 6 2x-6 = 3x-c 2x-6 = d(x-x) f(x-3) =g

User Windsor
by
4.4k points

2 Answers

6 votes

Answer:a= -1

b= -9

c=9

d=3

e=3

f=2

g=1.5

Explanation:

User Crosbie
by
5.1k points
3 votes

Answer:

a= -1

b= -9

c=9

d=3

e=3

f=2


g=\frac32

Explanation:

Rule of sign:

  1. (-)×(+)=(-), (-)÷(+)=(-)
  2. (+)×(-)=(-) , (+)÷(-)=(-)
  3. (+)×(+)=(+), (+)÷(+)=+
  4. (-)×(-)=(+), (-)÷(-)=(+)

Given that,


(3x)/(2x-6)+(9)/(6-2x)

We can rewrite 6-2x as 2x-6, taking (-1) as common factor of (6-2x)


=(3x)/((2x-6))+(9)/(-1(2x-6))

So, a= -1


\frac9{-1}=-9


=(3x)/((2x-6))+(-9)/((2x-6))

So, b= -9

The L.C.M of (2x-6) and (2x-6) is (2x-6)

and (2x-6)÷(2x-6)=1


=(1 * 3x+1* (-9))/((2x-6))


=(( 3x-9))/((2x-6))

∴c= 9

(3x-9) has a common factor 3 and (2x-6) has a common factor 2.

(3x-9)=3(x-3)

(2x-6)=2(x-3)


=(3(x-3))/(2(x-3))

∴d=3, e=3 and f=2

Since the denominator and numerator are the product of two polynomial. So, if there is any common element, then can cancel the common factor.

Here the common factor is (x-3). So cancel out (x-3).


=\frac32


\therefore g=\frac32

User Unarity
by
4.9k points